Performance Determinants Of Village Government Apparatus In Rupat Utara District - Elsyahpitri, Sonia; Agustiawan, Agustiawan; Putri, Annie Mustika (INTERNATIONAL JOURNAL OF TRENDS IN ACCOUNTING RESEARCH, 2023)
This final thesis/task discusses how the performance of village government officials in Rupat Utara sub-district, Bengkalis district in running good village government. Village government performance which is categorized as good can be influenced by several aspects or factors in it, namely public accountability, work ability, organizational culture, and supervision. This type of research is quantitative with data collection methods using questionnaires. The population of this study were eight villages in North Rupat District, Bengkalis Regency. And the sample selected was 64 respondents using purposive sampling method. The results showed that public accountability, work ability, organizational culture, and oversight had a positive and significant effect on the performance of village government officials. This research is expected to provide benefits for village apparatus in making every decision and make individuals responsible and can become an evaluation for the future so that it will be even better.